1996
DOI: 10.1101/gad.10.23.2949
|View full text |Cite
|
Sign up to set email alerts
|

The retinoblastoma gene product protects E2F-1 from degradation by the ubiquitin-proteasome pathway.

Abstract: E2F-1 plays a crucial role in the regulation of cell-cycle progression at the G1-S transition. In keeping with the fact that, when overproduced, it is both an oncoprotein and a potent inducer of apoptosis, its transcriptional activity is subject to multiple controls. Among them are binding by the retinoblastoma gene product (pRb), activation by cdk3, and S-phase-dependent down-regulation of DNA-binding capacity by cyclin A-dependent kinase. Here we report that E2F-1 is actively degraded by the ubiquitin-protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
190
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(213 citation statements)
references
References 62 publications
19
190
1
3
Order By: Relevance
“…The expression of E2F1 and pRb was confirmed by Western blot analysis (top panel in Figure 1A, panel A3). Of note, pRb could stabilize the protein level of E2F1 (top panel in Figure 1A, panel A3), which is consistent with previous reports [33][34][35]. In addition, the E2F1 mutant [E2F1(E132)] lacking DNA-binding activity failed to transactivate pVHL promoter activity ( Figure 1A, panel A4), which suggested that the DNA-binding activity of E2F1 was required for activating pVHL.…”
Section: Results Pvhl Is a Direct Downstream Target Of E2f1supporting
confidence: 89%
“…The expression of E2F1 and pRb was confirmed by Western blot analysis (top panel in Figure 1A, panel A3). Of note, pRb could stabilize the protein level of E2F1 (top panel in Figure 1A, panel A3), which is consistent with previous reports [33][34][35]. In addition, the E2F1 mutant [E2F1(E132)] lacking DNA-binding activity failed to transactivate pVHL promoter activity ( Figure 1A, panel A4), which suggested that the DNA-binding activity of E2F1 was required for activating pVHL.…”
Section: Results Pvhl Is a Direct Downstream Target Of E2f1supporting
confidence: 89%
“…Alternatively, Rb may compete with some other proteins involved in the degradation pathway which bind to the same or similar sites of mdm2 to mediate its ability to target p53 for degradation (Figure 1). The ability of Rb to prevent protein degradation through proteinprotein interaction has been demonstrated with E2F1 (Campanero and Flemington, 1997;Hateboer et al, 1996;Hofmann et al, 1996). Whether common mechanisms exist for Rb in preventing protein degradation remain to be seen.…”
Section: Rb Apoptosismentioning
confidence: 99%
“…Previous work in which E2F proteins were highly overexpressed by transient transfection have demonstrated that E2F-1 and E2F-4 have the potential to be degraded by the ubiquitin ± proteosome pathway (Hateboer et al, 1996;Hofmann et al, 1996). It is quite possible that the rapid degradation of E2F-3 in cell cycle stages other than S phase is mediated by the ubiquitin ± proteosome pathway.…”
Section: The Half-life Of E2f-3 Increases During S Phasementioning
confidence: 99%